Determination of Kinship among Orange Cultivars (Citrus sp.) Based on Flavonoid Profiles - Watuguly, Theophilus Wilhelmus; Thenu, Rettodwikart (Universitas Pattimura, 2025)
Orange (Citrus sp.) is a type of plant with a superior flavor and aroma of the fruit that satisfies many tastes in Indonesian society. As one of the exceptional fruit commodities, it has economic advantages and vast marketing. Increase public awareness of the need for a source of nutrition and the benefits generated by the orange as having antioxidant, antibacterial, antiviral, hypo-allergenic, and anticancer activity, as well as industrial raw materials such as jam, juice, syrup, and deodorizer. To measure the kinship of orange species based on flavonoid content. Exploration was carried out in a basic chemical laboratory, the parameters measured were the flavonoids by using the wavelength of maximum absorption of the UV-Vis spectrophotometry of citrus flavonoids. Furthermore, profile flavonoids with UV-Vis spectrophotometry include absorption bands of the type of flavonoid. Data analysis and results of chemical constituents in the form of a binary data matrix. After that, proceed with the analysis SIMQUAL (Similarity of Qualitative Data) to obtain a similarity matrix between phenetic cultivars of orange. The phenetic similarity matrix and the clustering analysis method (Sequential Agglomerative Hierarchical and Nested), the SAHN-UPGMA (Unweighted Pair-Group Method Arithmetic Average) program, and NTSys-PC v.2.0 were used to construct the phenetic family tree (dendrogram). The result showed that by using the UV-Vis spectrophotometry profile of flavonoids, a dendrogram is formed of two main clusters: Cluster I, which consists of sweet orange cultivars, ‘Kisar’ grapefruit, sour orange, lemon, ‘suanggi’ orange, and pomelo; Cluster II consists of limau orange and lime cultivars. Flavonoid profiles using UV-Vis spectrophotometry indicate that ‘Kisar’ grapefruit and lemon have similarity coefficient of 0.88, which means close kinship with limau and lime, which have a coefficient of 0.88, meaning close kinship with cluster II. Reagent NaOH 40%, AlCl₃ 5%, and NH₃ 25% can produce color changes that indicate the presence of flavonoid content, while using distilled water does not. The kinship test consists of 2 clusters that have a difference of 0.52 (52%). This study provides a novelty approach to determining the phylogenetic relationships among Indonesian Citrus cultivars using UV-Vis spectrophotometry of flavonoid profiles, which has not been extensively applied in local Citrus diversity studies.